2007
DOI: 10.1016/j.jfms.2007.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriuria in cats with feline lower urinary tract disease: A clinical study of 134 cases in Norway

Abstract: Feline lower urinary tract disease (FLUTD) is considered to be one of the most common diagnoses in feline patients. Several authors have concluded that feline idiopathic cystitis is the most common cause of FLUTD, whereas infectious cystitis is diagnosed in only 2% of the cases. In the period from January 2003 to February 2005, 134 cats that presented with signs of lower urinary tract disorders were included in a study at the Norwegian School of Veterinary Science. Ninety-seven percent were first opinion cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 19 publications
6
77
1
4
Order By: Relevance
“…Urethral plugs have large amounts of matrix and minerals (usually struvite) and any crystalline material is disorganized. The general features of urolithiasis are similar for cats and dogs although struvite uroliths in cats are less associated with bacterial infections [6,7].Although the successful treatment of iFLUTD is often achieved with the removal of dry diets, stress reduction and increased water supply after re-canalization with indwelling urethral catheterization and warm saline flushing [5,7]. However, iFLUTD often re-occurs and progresses to refractory iFLUTD, which requires perineal urethrostomy to permanently relieve recurrent obstructions in male cats [5,7].…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…Urethral plugs have large amounts of matrix and minerals (usually struvite) and any crystalline material is disorganized. The general features of urolithiasis are similar for cats and dogs although struvite uroliths in cats are less associated with bacterial infections [6,7].Although the successful treatment of iFLUTD is often achieved with the removal of dry diets, stress reduction and increased water supply after re-canalization with indwelling urethral catheterization and warm saline flushing [5,7]. However, iFLUTD often re-occurs and progresses to refractory iFLUTD, which requires perineal urethrostomy to permanently relieve recurrent obstructions in male cats [5,7].…”
mentioning
confidence: 96%
“…This has led to numerous terms such as feline urologic syndrome (FUS), feline interstitial cystitis (FIC; based on similarities with the human condition) and idiopathic feline lower urinary tract disease (iFLUTD) [8,16]. It is reported that 70% of non-obstructive LUTD is idiopathic and that 25% is due to cystoliths [6]. Obstructive causes of LUTD are usually intraluminal with the majority caused by urethral plugs rather than uroliths.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Estudos recentes indicam que E. coli e Staphylococcus felis, além de Enterococcus faecalis são os uropatógenos mais comuns em gatos com SDTUI (EGGERTSDÓTTIR et al, 2007;LITSTER et al, 2007;SAEVIK et al, 2011). Dos sete gatos com a cistite bacteriana, quatro tinham infecção por E. coli e três por Staphylococcus spp.…”
Section: Resultsunclassified
“…No entanto, todos esses animais haviam sido submetidos à sondagem uretral prévia para desobstrução, o que fatalmente poderia ter propiciado a instalação e proliferação dos agentes infecciosos . Eggertsdóttir et al (2007) verificaram que 33% dos gatos da Noruega com DTUIF tinham bacteriúria que excedeu 103 UFC/ml, e em 25% desses gatos, a bacteriúria excedeu 104 UFC/ml, sem diferença significativa quanto ao método de coleta para cultura, e sendo mais freqüente em fêmeas. Os autores relacionaram este alto índice com a possibilidade de infecção secundária ao comportamento de acasalamento, já que na Noruega, a maioria dos gatos tem acesso ao exterior das casas, que é intensificado em épocas de verão.…”
Section: Os Agentes Mais Comuns Em Itu São Bactérias Aeróbias Princiunclassified